Zooplankton Composition in the Southwestern Sea of Marmara During the Summer Season - Dalida Bedikoğlu; Sandra Jerinić; Nazli Demirel (Çanakkale Onsekiz Mart University Journal of Marine Sciences and Fisheries)
The Sea of Marmara (SoM) is a highly sensitive semi-enclosed marine ecosystem that has been undergoing considerable ecological changes in the recent decades. This study aimed to evaluate the summer zooplankton community structure via vertical hauls at 0-20 m depth in Erdek Bay, located in the southwestern part of the SoM, during two consecutive years, 2019 and 2020. The results revealed marked year-to-year shifts. In 2020, total zooplankton abundance declined markedly compared to 2019, primarily due to a sharp decrease in the abundance of Penilia avirostris, which was dominant in the community during 2019. Despite the higher abundance observed in 2019, diversity indices were lower, indicating that the community structure was largely shaped by the dominance of a single species. In contrast, unlike the Cladocera group, Copepoda abundance increased in 2020 compared to 2019. As the most recent data for this region date back to the early 2010s, this research provides an updated contribution to the understanding of summer zooplankton composition in Erdek Bay. The findings highlight the necessity for long-term zooplankton monitoring with high temporal resolution to better understand zooplankton dynamics in response to environmental changes in the southwestern part of the Sea of Marmara.